If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 6 = -12y + 62 Reorder the terms: 6 + 5y = -12y + 62 Reorder the terms: 6 + 5y = 62 + -12y Solving 6 + 5y = 62 + -12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12y' to each side of the equation. 6 + 5y + 12y = 62 + -12y + 12y Combine like terms: 5y + 12y = 17y 6 + 17y = 62 + -12y + 12y Combine like terms: -12y + 12y = 0 6 + 17y = 62 + 0 6 + 17y = 62 Add '-6' to each side of the equation. 6 + -6 + 17y = 62 + -6 Combine like terms: 6 + -6 = 0 0 + 17y = 62 + -6 17y = 62 + -6 Combine like terms: 62 + -6 = 56 17y = 56 Divide each side by '17'. y = 3.294117647 Simplifying y = 3.294117647
| 3x/4/10 | | p=5a-17 | | 24.039+6.016= | | x/3=2.13 | | T=n+7.25 | | H-62/5=5 | | 9=7b+7 | | 2y+9(8-4)=52 | | 7y+6=46+3y | | .45/x=2.05 | | 4e-16+5e=28 | | 40+5x=125 | | 10.358+2.416= | | 2k+7+8x=13 | | 10+x(x)=144 | | V+7=21 | | 8x^3=6x-8 | | 3x-2=4x+16 | | 4.5=-270h | | -8y+20=-4(y-8) | | 3x+2y+50=310 | | 2tan(x)sin(2x)=3 | | 3(2x+4)=78 | | 2x+6=128 | | 3c+10=16 | | .8k=19.2 | | N/6=5/15 | | x(5x+3)=2x^2-7x+8 | | -8+2n+14=-2n+4 | | -8+2n+14=-2a+4 | | 2x(3x-2x)=0 | | 5x^4-10x^3+3x^2=6x |